The Effect of Financial Education on the FinancialLiteracy of the Millennial Generation - Choirul Anwar, Mohamad; Nurfattah, Arizqiya; Maqsudi, Achmad (PT. Anagata Sembagi Education, 2024)
This study aims to analyze the influence of financial education on the financial literacy of the millennial generation. Millennials face increasingly complex financial challenges as access to digital financial products and consumptive lifestyles increases. Good financial literacy is needed so that they are able to make wise financial decisions, save, and invest for the future. This study uses a quantitative approach by collecting data through a survey involving 121 millennial respondents who have participated in financial education programs. Data analysis was carried out using SPSS version 25 software and linear regression methods to test the relationship between financial education and financial literacy levels. The results of the study show that financial education has a significant positive influence on millennial financial literacy. These findings underscore the importance of financial education programs in improving the financial understanding of millennials so that they are better prepared to face complex financial decisions. This research is expected to be a reference for policymakers and educational institutions in designing more effective financial literacy programs to support the financial well-being of the millennial generation.